Pengaruh Stres Kerja dan Kepuasan Kerja terhadap Turnover Intention dengan Komitmen Organisasi sebagai Variabel Intervening pada Karyawan PT. X - Salsa Bela Rahmi; Hardani Widhiastuti; Rusmalia Dewi (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
Study aims to analyze effect of work stress and job statisfaction on turnover intention with organizational commitement as an intervening variable among employees of PT. X. Number respondents this study were 260 employees of PT. X. Research sample was taken using purposive sampling. Retrieval research data uses a scale work stress, job statisfaction, turnover intention and organizational commitment. Data analysis uses SmartPLS program. The results of the study indicate show that work stress has a significant effect on turnover intention, indicated by a p-value of 0.000<0.05. Job satisfaction has a significant effect on turnover intention with a p-value of 0.002<0.05. Organizational commitment has a significant effect on turnover intention with a p-value of 0.000<0.05. Work stress has a significant effect on organizational commitment with a p-value of 0.000<0.05. Job satisfaction has a significant effect on organizational commitment with a p-value of 0.000<0.05. There is an effect of work stress on turnover intention through organizational commitment as an intervening variable. There is also an effect of job satisfaction on turnover intention through organizational commitment as an intervening variable for employees at PT. X.